1999
DOI: 10.1021/bi991352p
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically Inactive Macrophage Migration Inhibitory Factor Inhibits Monocyte Chemotaxis and Random Migration

Abstract: Macrophage migration inhibitory factor (MIF) is a cytokine that was first described as an inhibitor of the random migration of monocytes and macrophages and has since been proposed to have a number of immune and catalytic functions. One of the functions assigned to MIF is that of a tautomerase that interconverts the enol and keto forms of phenylpyruvate and (p-hydroxyphenyl)pyruvate and converts D-dopachrome, a stereoisomer of naturally occurring L-dopachrome, to 5,6-dihydroxyindole-2-carboxylic acid. The phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
76
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 34 publications
(73 reference statements)
1
76
1
1
Order By: Relevance
“…It might be that its presence with ␤-cells encompasses also the limitation of infiltrating monocytes. It is worth noting that some studies recently demonstrated that MIF also inhibited the MCP-1-induced migration of monocytes (56,57). In addition, we do not know which is the amount of MCP-1 released by islet in vivo and if in physiological condition is sufficient to induce monocyte recruitment.…”
Section: Discussionmentioning
confidence: 86%
“…It might be that its presence with ␤-cells encompasses also the limitation of infiltrating monocytes. It is worth noting that some studies recently demonstrated that MIF also inhibited the MCP-1-induced migration of monocytes (56,57). In addition, we do not know which is the amount of MCP-1 released by islet in vivo and if in physiological condition is sufficient to induce monocyte recruitment.…”
Section: Discussionmentioning
confidence: 86%
“…Catalytically inactive HuMIF is greatly impaired in its ability to stimulate generation of superoxide in activated neutrophils (37); thus, the reduced tautomerase activity of TvMIF could decrease the molecule's priming of host neutrophils. Enzymatic tautomerase activity is not necessary for biological functions, such as macrophage migration, countering the effects of glucocorticoids, or growth regulatory and invasion-promoting properties (38)(39)(40). Thus, our further analyses have focused on characterizing possible biological functions of TvMIF that could contribute to prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…A standard biological activity of HuMIF is the ability to inhibit random migration of macrophages or monocytes (38,41). To determine whether TvMIF exerts this activity, we examined its effect on monocyte migration using a Boyden chamber assay.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the lack of an identified physiological substrate, whether tautomerase activity is a biologically relevant function of MIF is a matter of debate. On the negative side, P2 mutants retain MIF-like activity in assays of its proinflammatory action (52). However, others argue that the tautomerase active site may be critical for permitting and regulating interactions of MIF with receptors or binding proteins, including CD74 (41).…”
Section: Discussionmentioning
confidence: 99%